Opportunities for the Use of Brazilian Biomass to Produce Renewable Chemicals and Materials - Alarcon, Rafael T. [UNESP]; Lamb, Katie J.; Bannach, Gilbert [UNESP]; North, Michael (Wiley, 2021)
This Review highlights the principal crops of Brazil and how their harvest waste can be used in the chemicals and materials industries. The Review covers various plants; with grains, fruits, trees and nuts all being discussed. Native and adopted plants are included and studies on using these plants as a source of chemicals and materials for industrial applications, polymer synthesis, medicinal use and in chemical research are discussed. The main aim of the Review is to highlight the principal Brazilian agricultural resources; such as sugarcane, oranges and soybean, as well as secondary resources, such as andiroba brazil nut, buriti and others, which should be explored further for scientific and technological applications. Furthermore, vegetable oils, carbohydrates (starch, cellulose, hemicellulose, lignocellulose and pectin), flavones and essential oils are described as well as their potential applications.
Keywords: Brazilian crops; chemical industry; feedstocks; renewable materials; waste management